Modest Simultaneous Determination of Acetylsalicylic Acid and Salicylic Acid in Plasma by High Performance Liquid Chromatography UV Detection - Yahdiana Harahap (Journal of Global Pharma Technology, 2019)
Objective: Acetylsalicylic acid (ASA) is one of the drugs used in antiplatelet therapy. ASA is rapidly hydrolyzed to salicylic acid (SA) and has low levels in plasma. Analysis of ASA and SA in plasma has been done using LC-MS/MS, UHPLC, and HPLC with hydrolysis and fluorescence detector. Compared to those methods, HPLC equipped with UV detector is less expensive. The method using HPLC with UV detector also has been done but not sensitive enough according to the LLOQ. Therefore a sensitive and selective analysis method needs to be developed. This study aims to develop an analytical method of ASA and SA in human plasma using HPLC with UV detector.Method: The method used in this study is Reversed Phase - High Performance Liquid Chromatography using C18 column (Waters, Reliant™ 5 μm; 250 x 4.6 mm) with UV-Vis detector and was detected at wavelength of 230 nm. This method was developed using furosemide as internal standard (IS). Human plasma containing ASA and SA was extracted after protein precipitaion method using 15% perchloric acid with a liquid-liquid extraction method using ethyl acetate.Result: The method obtained was linear (r ≥ 0.99) at concentration range of 0.05 – 1.5 μg/mL for ASA and concentration range of 0.2 – 5.0 μg/mL for SA. The validation result of ASA and SA analytical method fulfilled the validation requirement of EMEA Bioanalytical Guideline in the year 2011. Therefore the method provides modest, sensitive, and selective measurements of ASA and SA concentrations.